Local gambling norms and audit pricing - Callen, Jeffrey L. (Journal of business ethics, 2020)
This study investigates whether local gambling norms are associated with audit pricing. Using a religion-based measure of local social gambling norms, we find strong evidence that public firms located in U.S. counties with more liberal gambling norms exhibit higher levels of audit fees. This result is consistent with our view that, as an important external risk factor, clients’ local gambling norms influence audit pricing decisions. Our findings are robust to a battery of sensitivity tests, including non-religion based measures of liberal gambling norms and a natural experiment.